Analisis kesesuaian Hukum Islam dan Hukum Positif tentang Praktik Perkawinan Paksa: Desa Gunung Eleh Madura - Achmad izzuddin Hanif; Achmad Ziyad Azka (Jurnal Hukum Lex Generalis, 2026)
This study aims to analyze the compliance of forced marriage practices in Gunung Eleh Village, Madura, with Islamic law and positive law. The study employs an empirical legal method with a qualitative approach through field data collection to identify the causal factors, impacts and legal consequences of this practice. The results indicate that forced marriage is still influenced by the culture of arranged marriages, obedience to religious leaders (kyai) and the community’s low levels of education, economic status and legal awareness. This practice has legal consequences because it violates positive law, specifically Article 6(1) of Law No. 1 of 1974 on Marriage and Articles 16(1) and (2) of the Compilation of Islamic Law, which require the consent of both prospective spouses. Meanwhile, from an Islamic legal perspective, this practice also violates one of the essential elements and requirements of marriage. Consequently, the marriage may be annulled by a court. This research is important for contributing to rural communities regarding the consent of prospective spouses as a form of protection for women’s rights in the context of marriage.